Long-term outcomes in ypT0 rectal cancers: An international multi-centric investigation on behalf of Italian Society of Surgical Oncology Young Board (YSICO). Issue 8 (August 2017) - ,; Delrio, P.; D'Ugo, D.; Balducci, G.; Montesi, G.; Muratore, A.; Poblador, A.R.; Persiani, R.; Frasson, M.; Roviello, F.; Vincenti, L.; Trompetto, M.; et al.
Abstract: Aim: To investigate the outcome and pattern of survivals of rectal cancer patients presenting a complete or nearly complete tumor response after neo-adjuvant treatment. Methods: Young surgeons <40 years old affiliated to the Italian Society of Surgical Oncology (YSICO) from 13 referral centers for colorectal cancer treatment, were invited to participate a retrospective study. Records from patients treated from 2005 to 2015 with a pathological diagnosis of ypT0/ypTis were retrieved and pooled in a common data-base for statistical purposes. All clinical and pathological variables were reviewed. Univariate and multivariate analyses were conducted with the end-point of survivals. Results: Two hundreds and sixty-one patients were analyzed including 237 ypT0 and 24 ypTis. Nodal positive patients were 8.7%. More than sixty-six percent of the patients did not perform adjuvant chemotherapy, with a statistical difference comparing N0 versus N+ patients (66.8% vs 40.9%, p 0.02). Mean follow-up was of 47.6 months. Twenty-two relapses were observed, 91.6% at a distant site. The mean time to recurrence was of 35.3 months. On univariate analysis, the use of adjuvant chemotherapy correlated with better OS exclusively in ypT0N + patients and not in ypT0N0. Univariate and multivariate analyses documented nodal positivity as the only prognostic factor correlated with a worse OS. Conclusion: Recurrences were mostly diagnosed at a distant site and within the third year of follow-up. Nodal positivity was the only variable independently correlated with a worse OS. Univariate analysis documented a benefit for the use of adjuvant chemotherapy treatment exclusively in ypT0N + rectal cancers.